MUSLIM DIGITAL MARKET FACEBOOK SEBAGAI MEDIA PROMOSI DAKWAH MELALUI KALIGRAFI - Fauziah, Rahmah El; Fatoni, Uwes (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The development of technology and the times force humans to adapt, including in preaching. Although new communication technology (da'wah transmission) cannot completely replace old technology, it can allow old technology to take on a new role. This causes moving with the times in the corridor of Islam so that it can develop in accordance with the methods of da'wah transmission, which includes the use of Facebook social media as a tool to promote da'wah through calligraphy, so this study reveals several things about the utilization of Facebook and cutting elements of da'wah based on the title